Keanekaragaman Lalat Buah (Diptera: Tephritidae) di Pertanaman Jeruk Manis di Kabupaten Bangka Tengah, Provinsi Kepulauan Bangka Belitung: Keanekaragaman Lalat Buah (Diptera: Tephritidae) di Pertanaman Jeruk Manis di Kabupaten Bangka Tengah, Provinsi Kepulauan Bangka Belitung - Herry Marta Saputra; Budi Afriyansyah (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Central Bangka Regency is one of central orange production in Bangka Belitung Islands Province. One of the important pests of sweet orange plants is fruit flies (Diptera: Tephritidae). This research aimed to study the diversity of fruit flies (Diptera: Tephritidae) on sweet orange plantations in Central Bangka Regency, Bangka Belitung Islands Province. The fruit flies were collected using Lynfield traps which installed in three villages producing sweet oranges in Central Bangka Regency. The types of attractants used to trap male fruit flies are methyl eugenol and cue lure. The fruit flies collected during the study were 4795 individuals, 3 genera, and 14 species. Fruit flies collected from the methyl eugenol were different compared to those collected using lure attractant trap. Most species (13 species) of fruit fly were found in Terentang village, and the rest was same (9 species). Bactrocera carambolae and B. dorsalis were the dominant fruit fly species in the three research locations.